2015
DOI: 10.1063/1.4921745
|View full text |Cite
|
Sign up to set email alerts
|

High-endurance megahertz electrical self-oscillation in Ti/NbOx bilayer structures

Abstract: Electrical self-oscillation is reported for a Ti/NbOx negative differential resistance device incorporated in a simple electric circuit configuration. Measurements confirm stable operation of the oscillator at source voltages as low as 1.06 V, and demonstrate frequency control in the range from 2.5 to 20.5 MHz for voltage changes as small as ∼1 V. Device operation is reported for >6.5 × 1010 cycles, during which the operating frequency and peak-to-peak device current decreased by ∼25%. The low operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 25 publications
(24 reference statements)
0
55
0
Order By: Relevance
“…It has been reported that the oscillation frequency of MIT devices with the circuit configuration in Fig. 2(b) can be up to several 10's to 100's MHz [20,22]. It is highly probable that the reported frequency is limited by the parasitic RC delay in the off-chip electrical measurement setup.…”
Section: B Effect Of Intrinsic Transition Timementioning
confidence: 99%
“…It has been reported that the oscillation frequency of MIT devices with the circuit configuration in Fig. 2(b) can be up to several 10's to 100's MHz [20,22]. It is highly probable that the reported frequency is limited by the parasitic RC delay in the off-chip electrical measurement setup.…”
Section: B Effect Of Intrinsic Transition Timementioning
confidence: 99%
“…16,17 Relaxation oscillators that are constructed with NbO2 or VO2 typically use a DC-current or voltage driven Pearson-Anson-like circuit that includes a capacitor in parallel with the NDR element, and a suitable series resistor. 15,[18][19][20][21][22] However, generation of fast DC-voltage-driven periodic spiking will require aggressive scaling to minimize both the electrical and thermal time constants of these oscillators, 11,23 for instance, by careful electron-beam lithography, which may not be practical for largescale electronics.…”
mentioning
confidence: 99%
“…[14][15][16] Within the region of negative differential resistance, the current remains unstable and self-sustained current oscillations can be generated. 12,16 The high MIT temperature of NbO 2 favors fast switching and high frequency current oscillations because the device can cool quickly below T MIT .…”
mentioning
confidence: 99%
“…9 Reversible threshold switching in current has been reported mostly using amorphous NbO 2 films, where the current turns off immediately after lowering the input voltage (V in ) below the threshold voltage (V th ). 3,[10][11][12][13] Current-voltage (IV ) characteristics usually exhibit current-controlled (s-type) negative differential resistance (dV /dI < 0) while switching from a low current semiconducting to a high current metallic state. [14][15][16] Within the region of negative differential resistance, the current remains unstable and self-sustained current oscillations can be generated.…”
mentioning
confidence: 99%